2017
DOI: 10.1186/s12891-017-1595-0
|View full text |Cite
|
Sign up to set email alerts
|

Generalised joint hypermobility and shoulder joint hypermobility, – risk of upper body musculoskeletal symptoms and reduced quality of life in the general population

Abstract: BackgroundGeneralised Joint Hypermobility (GJH) is a hereditary condition with an ability to exceed the joints beyond the normal range. The prevalence of GJH in the adult population and its impact on upper body musculoskeletal health and quality of life has mostly been studied in selected populations. The aims of this study were therefore, firstly to study the prevalence of GJH and GJH including shoulder hypermobility (GJHS), in the general Danish adult population; secondly to test the associations between GJH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
(67 reference statements)
4
14
1
1
Order By: Relevance
“…(28) Previous studies confirm the link between quality of life and musculoskeletal disorders. (29)(30)(31) The result of this study is the same with the study in Japan. The results of Pearson correlation coefficient show that there is a significant correlation between the scores of the GLFS-25 and EQ-5D (r= 0.85, p= 0.01).…”
Section: Discussionsupporting
confidence: 78%
“…(28) Previous studies confirm the link between quality of life and musculoskeletal disorders. (29)(30)(31) The result of this study is the same with the study in Japan. The results of Pearson correlation coefficient show that there is a significant correlation between the scores of the GLFS-25 and EQ-5D (r= 0.85, p= 0.01).…”
Section: Discussionsupporting
confidence: 78%
“…GJH with such symptoms has recently been classified as hypermobility spectrum disorder (HSD) [11]. Several studies have found that people with HSD combined with shoulder symptoms report lower health-related quality of life than healthy controls [5,6,12].…”
Section: Introductionmentioning
confidence: 99%
“…In specific conditions, a standardised questionnaire can be used 10. The prevalence of GJH ranges from 2% to 57%, depending on the definition and methods used 11–14. A large, recent study of a general Danish population found that the self-reported prevalence of GJH and knee joint hypermobility was 13% and 23%, respectively 15.…”
Section: Introductionmentioning
confidence: 99%